Gender Matters: Understanding Transitions in Surgical Education - Offiah, Gozie; Cable, Stuart; Rees, Charlotte E.; Schofield, Susie J. (Frontiers in Medicine, 2022)
Introduction Diverse transitions are elemental to medical career trajectories. The effective navigation of such transitions influences a sense of belonging and wellbeing, positive relationships, and good engagement and attainment within new contexts. Using Multiple and Multidimensional Transitions (MMT) theory as an analytical lens, this paper aims to answer the research question: “What gendered transitions do female surgeons experience, and how do these gendered transitions impact them?” Methods We conducted a qualitative study drawing on narrative inquiry, with face-to-face and online semi-structured interviews with 29 female surgeons across nine surgical specialities in Ireland and Scotland. This paper is part of a larger study including male surgeons, other colleagues and patients of female surgeons. The female surgeons in this paper were purposively sampled using maximum variation sampling across several levels (consultants, trainees and middle-grade doctors), as well as six who had transitioned out of surgery. Framework analysis was employed to interrogate the interview data. Results Five overarching types of transitions were identified across surgical education but only three of these transitions—work, culture and health—were primarily experienced by female surgeons (not male surgeons so were considered gendered), thereby impacting social, academic, and psychological domains. The remaining two types of transition—education and geography—were seemingly experienced equally by female and male surgeons, so are beyond the scope of this paper focused on female surgeons’ gendered experiences. Conclusion This novel qualitative study drawing on MMT theory illustrates how multiple gendered transitions interact and impact female surgeons across the surgical education continuum. Aligned with MMT theory, family members and others are also purportedly affected by female surgeons’ transitions. Healthcare educators, leaders and policymakers need to better understand gendered transitions and their impacts to improve support for female surgical trainees on their educational journeys.